Shall Migraine be Considered a Simple Benign Headache Disorder? - Saqr, Mohammed (International Journal of Health Sciences, 2008)
Abstract: Migraine is a primary headache disorder which has received little attention from health care policies and physicians. This has led to ineffective management and more suffering to the patients and society. Migraine per se is a disabling disease which has its impact on the patient, family and work. It is associated with high incidence of psychiatric co-morbidities, especially depression and anxiety as well as other mental disorders. Depression affects around 80% of chronic migraineurs, an association that adds to the suffering. It has been conïƒžrmed as risk factors for developing radiographic and clinically evident ischemic cerebrovascular infarctions. Lately, it was associated with angina, myocardial infarction and intracerebral hemorrhage. Migraine plays a central role in the pathogenesis of these diseases, not just a simple association. These comorbidities and the disabilities migraine makes should change our views of migraine as a simple headache disorder, and directs our efforts to a better recognition and an effective management for the prevention of the disease associated morbidity.